2018
DOI: 10.1037/aap0000096
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of the model minority myth, school racial composition, and psychological distress among Asian American adolescents.

Abstract: The authors investigated the moderating effect of school racial composition in the relationship between internalization of the model minority myth and psychological distress among Asian American adolescents. The model minority myth is the stereotype of Asian Americans as more successful than other racial minority groups because of values emphasizing hard work, achievement, and belief in the "American dream" (Yoo, Burrola, & Steger, 2010). The following 2 aspects of this myth were assessed: the myth of achievem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 34 publications
6
87
0
Order By: Relevance
“…For Asian Americans, failure to meet the educational expectations of this stereotype may result in feelings of inadequacy, self-doubt, psychological distress, and suicide (Kim & Park, 2008). Atkin, Yoo, Jager, and Yeh (2018) recently reported that Asian Americans who internalize model minority stereotypes might feel burdened due to the pressure they feel to live up to societal expectations of being successful, intelligent, and hardworking. As a result, when Asian Americans receive praise for something they have accomplished, they might be afraid of not living up to others’ expectations of them (i.e., impostor feelings).…”
Section: Impostor Phenomenon and Psychological Distressmentioning
confidence: 99%
“…For Asian Americans, failure to meet the educational expectations of this stereotype may result in feelings of inadequacy, self-doubt, psychological distress, and suicide (Kim & Park, 2008). Atkin, Yoo, Jager, and Yeh (2018) recently reported that Asian Americans who internalize model minority stereotypes might feel burdened due to the pressure they feel to live up to societal expectations of being successful, intelligent, and hardworking. As a result, when Asian Americans receive praise for something they have accomplished, they might be afraid of not living up to others’ expectations of them (i.e., impostor feelings).…”
Section: Impostor Phenomenon and Psychological Distressmentioning
confidence: 99%
“…Thirteen studies published over twenty-five years met inclusion criteria, an indication that more research is needed, particularly as schools are becoming more diverse yet segregated over time. The evidence thus far supports the protective association of having higher same-race/ethnic group density for all students, with the exception of one study (Atkin, 2018). In contrast, there was no overall strong evidence of mental health advantage in schools with greater diversity.…”
Section: Discussionmentioning
confidence: 76%
“…While the majority included high-school adolescent samples (n = 8), two studies sampled middle-and high-school students, and three studies included middle-school adolescents only. Five studies examined the effects of race/ethnic density in the U.S. with three using nationally representative school-based data-National Longitudinal Study of Adolescent Health (Add Health; Crosnoe, 2009;Walsemann et al, 2011) and Department of Education's Office for Civil Rights (Coutinho, Oswald, & Forness, 2002), and two using convenience samples among adolescent girls of African descent (Seaton & Carter, 2018) and Asian-American adolescents (Atkin, 2018). Three studies examined density effects using European data sources (Astell-Burt, Maynard, Lenguerrand, & Harding, 2012;Eilbracht, Stevens, Wigman, van Dorsselaer, & Vollebergh, 2015;Gieling, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the previous ones, in this group, no connection difficulties have been observed, although their parents' understanding of the language has. However, in this situation, above all, it has affected the socialization of Asian students, who were already characterized by having poor social skills [79]. This has been associated with few interactions in the different schools' digital media [80].…”
Section: Online Teaching and Its Inference In The Social Problems Of Intercultural Studentsmentioning
confidence: 99%